(untitled) (Annual of the Faculty of Philosophy in Skopje, 2019)
Three determinants shape the role and influence of the EU as a global-regional actor in peace and security: capacity (institutional, material, human and operational, as well as financial) to undertake missions; willingness to devote resources to security and defence purposes, mainly driven by member states’ priorities; and acceptance (internal and external) of the EU as a leading actor in peace and security. The institutional security and defence framework of the EU has undergone many reforms in the past three decades. The beginnings of this process have been established by the Treaty of Maastricht (1992) that has established the EU Common Foreign and Security Policy (CFSP). By the Stabilization and Association Agreement entering into force, R.N. Macedonia has officially confirmed its determination for moving closer to the CFSP goals. Therefore, the paper analyses the process that R.N. Macedonia is implementing regarding this issue, as well as it faced challenges.